Sosialisasi E-Commerce Sebagai Media Pemasaran Produk UMKM Masyarakat Desa Muara Basung Kecamatan Pinggir - Budy Satria; Yessi Ratna Sari; Teuku Radillah; Leonard Tambunan; Hafiz Mursalan; Muhammad Iqbal (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2022)
Muara Basung Village is one of the villages located in the suburbs, Bengkalis Regency, Riau Province. Based on data in the field, the problem that occurs is that there are still many MSME actors in the village of Muara Basung having difficulty running a sales system using online marketing strategies with the aim of making it accessible to many people. One of the online marketing strategies is to use digital marketing, namely e-commerce. Based on these conditions, Institut Teknologi Mitra Gama works as one of the universities based in the field of information technology in collaboration with the Bengkalis Regency Youth Organization to carry out community service programs in the form of assistance to introduce E-Commerce. The service method used is data collection, technical preparation, implementation and evaluation of activities. The performance indicators prove that this activity is proceeding according to the initial plan. The result of this activity is that the participants are very enthusiastic about getting to know E-Commerce to market their products so that they can be reached more widely by potential buyers. The continuation of this activity is expected that every participant will switch to online marketing media for a wider reach in finding potential buyers. Thus the participants become aware of the importance of learning information technology to increase competitiveness, especially in selling MSME products.